Проблеми анонімності власників електронних грошей: юридичний аспект - Шульгін, Андрій Артурович; Шульгін, А. А.; Shulgin, Andrew (ВД "Гельветика", 2020)
Статтю присвячено проблемі анонімності власників електронних грошових коштів та способам захисту їх прав. Зазначено, що популярність такого питання пов’язана перш за все із криптографічним захистом від підробки електронних грошей, можливістю здійснення транзакцій анонімно, а також можливістю зменшити ризики валютних коливань, які відбуваються на сучасному валютному ринку. Встановлено, що анонімне використання Інтернету і використання шифрування особистих даних і засобів комунікації є невіддільним правом людини. Встановлено, що чинним законодавством України не передбачено чіткий перелік документів, які могли б встановити особу, зазначено, що такий перелік існує виключно за певних юридичних подій, зокрема вчинення нотаріальних дій.

The article is devoted to the issue of anonymity of electronic money (digital currency) owners and how to protect their rights. It is noted that the popularity of such electronic money is primarily associated with cryptographic protection against counterfeiting electronic money, the ability to conduct transactions anonymously, as well as the ability to reduce the risks of currency fluctuations that occur in the modern foreign exchange market. It has been established that the anonymous use of the Internet and the use of encryption of personal data and means of communication is an inalienable human right. Actual problems of anonymity of Internet users are disclosed, since electronic money users are also Internet users, the main problems are the low level of state control on private entities that actually administer the Internet space; the problem of requesting information from service providers of the corresponding services. It is proved that the electronic money operator provides users with the right to anonymity until certain legal events occur: reaching a limit when making settlements or storing funds in an account; violation of the rights of other users. It was determined that the main problem of the anonymity of the owners of electronic funds is the impossibility of identifying the person according to the information that was necessary when registering or creating an electronic wallet. It is concluded that it is only in court that it is possible to identify a person by the evidence submitted by the parties to the process. It was determined that electronic money operators, on the basis of internal rules, created an independent system of user identification by analyzing and summarizing approaches to user identification by such international electronic money operators as PayPal, Webmoney, GlobalMoney, in particular, in the same way in which the user performed the initial registration account and e-wallet. In case of loss of access to the account, the user can attribute it in the following ways: providing a permanent or temporary password for access to the account via mobile phone or e-mail; indication of secret access codes. It is proved that the current legislation of Ukraine does not provide a clear list of documents that could establish an identity, it is indicated that such a list exists only in certain legal events, in particular, notarial acts.
Шульгін, А. А. Проблеми анонімності власників електронних грошей: юридичний аспект / А. А. Шульгін // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 65-69.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; електронні гроші; гроші; анонімність; ідентифікація; грошовий обіг; теорія грошей; речі; об’єкти цивільних прав; майнові права; digital currency; money; anonymity; identification; money circulation; money theory; goods; civil rights; property rights